RELATIONSHIP BETWEEN AGE, GENDER, AND MULTIMORBIDITY WITH LENGTH OF HOSPITAL STAYIN ELDERLY PATIENTS - Xuan, Nguyen Thanh; Luyen, Nguyen Van; Thuan, Nguyen Van; Thao, Pham Ngoc; Long, Dao Duc (Journal of Health and Aging, 2025)
To evaluate the relationship between age, sex, and multimorbidity with hospital length of stay among elderly inpatients. A retrospective cross-sectional study was conducted on 507 medical records of patients aged ≥60 years admitted to the Senior Officer Department, 103 Military Hospital, between December 2022 and October 2024. Data were analyzed using SPSS version 26.0. One-way and two-way ANOVA were performed to examine the effects of age, sex, and comorbidity burden on hospital stay. Male patients had longer hospital stays (10.68 ± 6.24 vs. 9.40 ± 4.95 days) and a higher mean number of comorbidities (3.57 ± 1.70 vs. 3.26 ± 1.69; both p < 0.05) compared with females. Hospital stay increased with advancing age, from 9.27 ± 5.78 days in the 60–69 age group to 11.07 ± 5.54 days in the 80–89 age group (p < 0.001). Similarly, the number of comorbidities rose with age, from 2.84 ± 1.48 to 4.24 ± 1.93 (p < 0.001). Two-way ANOVA confirmed significant effects of both age (p < 0.001) and sex (p = 0.033) on comorbidity burden, whereas the interaction effect was not significant (p = 0.091). For hospital stay, comorbidity burden was the main determinant (p < 0.001), with no significant sex effect (p = 0.09). Patients with ≥6 comorbidities had markedly prolonged hospital stays, irrespective of sex. Age and multimorbidity are the principal determinants of hospital stay duration in elderly patients. While males showed a higher comorbidity burden, the effect of sex on hospital stay was largely explained by multimorbidity. These findings underscore the importance of comprehensive comorbidity management to reduce hospital stay and optimize care for older adults.